EXPLORING FIRM VALUE IN SUSTAINABILITY ERA : FINANCE, GOVERNANCE, AND ESG - Himmatul Ulya Dynopha; Taufiq Arifin (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
In the sustainability era, firm value is increasingly shaped not only by financial performance but also by governance practices and Environmental, Social, and Governance (ESG) disclosure. Although extensive research has examined the ESG and firm value relationship, most studies rely on empirical firm-level analyses without systematically synthesizing the intellectual structure and thematic evolution of the field. Addressing this gap, this study conducts a comprehensive bibliometric analysis of 775 global publications from 2015 to 2024 using VOSviewer to map research trends, collaboration networks, and thematic clusters. The findings reveal that sustainability has become a central pillar in value creation, with ESG disclosure and governance mechanisms functioning as key determinants and moderating dimensions. The novelty of this research lies in its integrative perspective, which unifies financial, governance, and sustainability dimensions within a single analytical framework, offering deeper insights into the multidimensional drivers of firm value. These results contribute to theory development and provide practical guidance for long term strategic decision making